2010
DOI: 10.3201/eid1608.091847
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic (H1N1) 2009 Surveillance for Severe Illness and Response, New York, New York, USA, April–July 2009

Abstract: Health departments need the capacity to rapidly expand and modify surveillance during a changing outbreak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 13 publications
2
41
1
Order By: Relevance
“…We found that during the pandemic period 17% of overall pH1N1 infected cases were children ( < 12 years). This observation agrees with the published data from China and neighboring countries [7,21] but is in contrast with that of North America where pediatric infections were more prevalent [22,23].…”
Section: Discussioncontrasting
confidence: 47%
“…We found that during the pandemic period 17% of overall pH1N1 infected cases were children ( < 12 years). This observation agrees with the published data from China and neighboring countries [7,21] but is in contrast with that of North America where pediatric infections were more prevalent [22,23].…”
Section: Discussioncontrasting
confidence: 47%
“…This association could not be entirely explained by access to care and underlying Disease surveillance in New York City (NYC) during the spring and summer of 2009 revealed an increased risk of hospitalization or death due to novel H1N1 influenza infection (2009 H1N1 influenza) among individuals of low socioeconomic status (SES). 1 Ageadjusted rates of hospitalization for 2009 H1N1 were significantly higher in high-poverty neighborhoods than in low-poverty neighborhoods; approximately half of hospitalized cases lived in low-income areas. 1 However, associations between poverty and severe 2009 H1N1 illness at the individual level were not understood.…”
mentioning
confidence: 99%
“…1 Ageadjusted rates of hospitalization for 2009 H1N1 were significantly higher in high-poverty neighborhoods than in low-poverty neighborhoods; approximately half of hospitalized cases lived in low-income areas. 1 However, associations between poverty and severe 2009 H1N1 illness at the individual level were not understood.…”
mentioning
confidence: 99%
“…During the pandemic, DOHMH discouraged diagnostic testing of mild ILI cases within the community and promoted empiric treatment for patients presenting with ILI symptoms. 1 Furthermore, not all participating clinics began diagnostic testing immediately, which potentially contributed to the low testing rate of ILI encounters. During the initial phase of this system's operation, data for 22 specimens were considered incomplete.…”
Section: Completenessmentioning
confidence: 99%
“…With onset of the 2009 pH1N1 outbreak, DOHMH also implemented enhanced citywide surveillance primarily for severe and hospitalized cases of influenza and ILI. 1 Because multiple respiratory viruses can cocirculate and present as ILI, 2,3 DOHMH collaborated with a network of community health centers, the Institute for Family Health (IFH), to implement a pilot respiratory virus surveillance system in ambulatory settings. This pilot surveillance system was designed to determine which respiratory virus strains were circulating in the community and link clinical and epidemiologic data in ambulatory electronic health records (EHRs) with respiratory virus diagnostic data to better characterize patients presenting with ILI.…”
mentioning
confidence: 99%